2016
DOI: 10.1007/s12041-016-0655-9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to larval crowding in Drosophila ananassae and Drosophila nasuta nasuta: increased larval competitive ability without increased larval feeding rate

Abstract: The standard view of adaptation to larval crowding in fruitflies, built on results from 25 years of multiple experimental evolution studies on Drosophila melanogaster, was that enhanced competitive ability evolves primarily through increased larval feeding and foraging rate, and increased larval tolerance to nitrogenous wastes, at the cost of efficiency of food conversion to biomass. These results were at odds from the predictions of classical K-selection theory, notably the expectation that selection at high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 53 publications
6
32
1
Order By: Relevance
“…Taken together, the results of Archana (2010), Sarangi et al (2015) and our study show that adaptation to larval crowding can occur through more than one set of mechanisms. Such alternative mechanisms of adaptation to crowding have been detected by multiple other studies (Joshi & Thompson, 1995;Joshi et al, 2001;Dey et al, 2012;Nagarajan et al, 2014). We now address each of our results individually and then discuss the possible reasons that might have led to the evolution of a different set of mechanisms in our populations.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Taken together, the results of Archana (2010), Sarangi et al (2015) and our study show that adaptation to larval crowding can occur through more than one set of mechanisms. Such alternative mechanisms of adaptation to crowding have been detected by multiple other studies (Joshi & Thompson, 1995;Joshi et al, 2001;Dey et al, 2012;Nagarajan et al, 2014). We now address each of our results individually and then discuss the possible reasons that might have led to the evolution of a different set of mechanisms in our populations.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, the mechanisms that underlie adaptations to larval crowding in the populations of Archana (2010) and Sarangi et al (2015) are very different from those found in the populations of Mueller et al (1993). Therefore, as suggested by other studies (Joshi & Thompson, 1995;Joshi et al, 2001;Dey et al, 2012;Nagarajan et al, 2014), there are multiple ways of adapting to larval crowding. Since in D. melanogaster, the larva is the chief feeding stage and larval resource acquisition plays a very important role in determining adult fitness components (Chippindale et al, 1993), it is quite possible that in the populations of Archana (2010), a very different suite of adult traits has evolved as a correlated response to selection (compared to the adult traits in the previous studies).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Rib o et al, 1989;Shenoi et al, 2016) show that the reproductive (adult) phase of D. melanogaster can be greatly affected by the developmental (larval) phase. Larval density affects adult life-history traits like body size (Miller & Thomas, 1958;Nagarajan et al, 2016), fecundity (Alpatov, 1932;Pearl, 1932), lifespan (Miller & Thomas, 1958;Economos & Lints, 1984;Zwaan et al, 1991) and reproductive success (Rib o et al, 1989). Males that develop under low larval density emerge as larger individuals, have higher mating success, mate at a faster rate and remate more often compared to smaller males that emerge from crowded cultures (Partridge & Farquhar, 1981, 1983Partridge et al, 1987a, b;Turiegano et al, 2013;Wigby et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In essence, density often determines the nature and intensity of selection acting on a population and has been studied within the broader premises of density dependent selection (MacArthur Wilson, 1967;Mueller, 1997;. Much of the existing literature investigated adaptation to increased (but stable) juvenile or adult density, using experimental evolution on laboratory populations of D. melanogaster (Mueller, Guo, & Ayala, 1991;Mueller & Sweet, 1986;Nagarajan, Natarajan, Jayaram, & Joshi, 2016;Sarangi, Nagarajan, Dey, Bose, & Joshi, 2016;. However, little is known about adaptation to fluctuating density.…”
Section: Introductionmentioning
confidence: 99%